Acarbose improves glycemic control as add-on or monotherapy in Indian type-2 diabetes: Findings from the GlucoVIP multinational observational study - Elizabeth Philip; Meenakshi L Sundaram; Rupam Das; Sushil Kumar Chauhan; Sandeep Deshpande; Sanjay Ambhore; Rahul Rathod; Pravin Manjrekar (Indian Journal of Endocrinology and Metabolism, 2013)
Objective: To investigate the efficacy and tolerability of the anti-diabetic agent acarbose (Glucobay® ) as add-on or monotherapy in a range of patients with type-2 diabetes mellitus (T2DM), including those with cardiovascular morbidities in India. Materials and Methods: This was a part of a prospective, non-interventional, non-controlled, multicentre, multinational, observational study. The study included patients of either gender if they were aged at least 18 years and had untreated or pre-treated type-2 diabetes mellitus (T2DM) or impaired glucose tolerance and no acarbose treatment within the 3 months before study inclusion. Results: In total, 1996 Indian patients were included in the effectiveness and 2010 in the safety analysis. Patients received acarbose (25-150 mg/day). The mean age of the patients was 50.1 years and the mean BMI was 27.2 kg/m 2 . Mean 2-h post-prandial plasma glucose (PPG) value and fasting blood glucose (FBG) decreased from 243.9 to 169.5 mg/dl and 158.3 to 120.4 mg/dl, respectively after the last follow-up of 12.4 weeks. The mean HbA1c value at initial visit was 8.4% and was 7.4% at the last follow-up visit. FBG, PPG and HbA1c deceased in 90.6%, 94.4% and 52.4% patients respectively, by the last follow-up visit. The mean decrease in weight and waist circumference was 1.4 kg and 1.6 cm, respectively by the last follow-up visit. Physicians assessed the efficacy of drug as positive response in "very good to good" in 91.08%, "sufficient" in 7.92% and "insufficient" in 0.90% of patients. Also, continuation of Acarbose was reported in 97.09% of patients. Adverse events were reported in 2.74% and drug-related adverse events were reported in 2.19% of patients. Majority of them were gastrointestinal adverse events but were not serious. Conclusion: Acarbose is effective and safe in Indian patients with T2DM. Further, it helps in weight reduction and has very good compliance in patients with T2DM.